2015
DOI: 10.4103/0970-1591.166481
|View full text |Cite
|
Sign up to set email alerts
|

Left retrocaval ureter without situs inversus or inferior venacava duplication

Abstract: Retrocaval ureter (pre-ureteral vena cava) is an uncommon congenital anomaly that causes ureteral obstruction by external compression. Although right retrocaval ureter is a common entity, left retrocaval ureter is extremely rare. A left retrocaval ureter is usually associated with situs inversus or duplicated inferior venacava (IVC). An isolated left retrocaval ureter with single left-sided IVC is even rarer and only four cases have been reported in the literature. We present images of a case with isolated lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…An isolated left retrocaval ureter with single left-sided IVC is very rare and only four cases have been reported in the literature. Thirugnanasambandam et al 3 reported a case of isolated left retrocaval ureter with a single left-sided IVC without situs inversus.…”
Section: Discussionmentioning
confidence: 99%
“…An isolated left retrocaval ureter with single left-sided IVC is very rare and only four cases have been reported in the literature. Thirugnanasambandam et al 3 reported a case of isolated left retrocaval ureter with a single left-sided IVC without situs inversus.…”
Section: Discussionmentioning
confidence: 99%
“…All retrocaval ureters found in our study were on the right. Left retrocaval ureter is associated with situs inversus, or duplicated or single left IVC [4,5,7,20,21,28,30]. In double IVC, the retrocaval ureter is present on the right or left side [4,5,7].…”
Section: Discussionmentioning
confidence: 99%
“…It is an exceptionally rare anomaly and associated with either complete or partial abdominal situs inversus, duplicated IVC or single left IVC. There are only nine cases of left retrocaval ureter published in the medical literature 6 7 8 9 10 11 12 13 14 ( Table 1 ). Among them, there is only one pediatric case: a 10-month-old girl with Goldenhar's syndrome, diagnosed during routine urological screening.…”
Section: Discussionmentioning
confidence: 99%